The Globalization of Care and the Situation of Slovenian Care Workers in Italy - Hrženjak, Majda (Two Homelands, 2014)
Based on individual interviews the author locates in contemporary global care economies Slovenian care workers who commute to Italy daily in order to perform cleaning and provide care for children and the elderly in private households. The main purpose is to identify the specific characteristics of informal care work in this micro border region between Italy and Slovenia, and to highlight the specific position of Slovenian care workers in global informal care markets. The analysis is based on 16 semi-structured interviews with female Slovenian citizens in the border region with Italy who commute daily to work in Italian households, and on current research on global care economies in Europe.